Marked Response in Microbial Community and Metabolism in the Ileum and Cecum of Suckling Piglets After Early Antibiotics Exposure - Yu, Miao; Mu, Chunlong; Zhang, Chuanjian; Yang, Yuxiang; Su, Yong; Zhu, Weiyun (Frontiers in Microbiology, 2018)
In modern swine husbandry systems, antibiotics have been used as growth promoters for piglets during sucking or weaning period. However, while early colonization of intestinal microbiota has been regarded crucial for the host’s later life performance and well-being, little is known about the impact of antibiotics on intestinal microbiota in sucking piglets. The present study aimed to investigate the effects of early antibiotics exposure on gut microbiota and microbial metabolism of suckling piglets. Sixteen litters of suckling piglets were fed a creep feed diet with (Antibiotic) or without (Control) antibiotics from postnatal day 7 to day 23 (n = 8). The ileal and cecal digesta were obtained for microbial composition and microbial metabolite analysis. The results showed that the antibiotic significantly altered the bacterial community composition by decreasing (P < 0.05) the diversity and richness in the ileum. The antibiotics significantly reduced the abundance of Lactobacillus in both the ileum and cecum, increased the abundance of Streptococcus, unclassified Enterococcaceae, unclassified Fusobacteriales, and Corynebacterium in the ileum, and the abundance of unclassified Ruminococcaceae and unclassified Erysipelotrichaceae in the cecum. The antibiotics decreased (P < 0.05) ileal lactate concentration and cecal concentration of total short-chain fatty acids (SCFA). But the antibiotics enhanced protein fermentation (P < 0.05) in the ileum and cecum, as ileal concentrations of putrescine and cadaverine, and cecal concentrations of isobutyrate, isovalerate, putrescine, cadaverine, spermine, and spermidine were significantly increased (P < 0.05). These results indicated that early antibiotics exposure significantly altered the microbial composition of suckling piglets towards a vulnerable and unhealthy gut environment. The findings provide a new insight on the antibiotics impact on neonates and may provide new framework for designing alternatives to the antibiotics towards a healthy practice for suckling piglets.